Economic aspects of wildlife farming: Analysis of household surveys from two Vietnamese provinces - Murphy, Mike; Hoffmann, Vivian; Ambler, Kate; Ha Thi Thanh Nguyen; Sinh Dang-Xuan; Hung Nguyen-Viet; Unger, Fred; Bett, Bernard K. (International Food Policy Research Institute, 2025)
Vietnam is a global hotspot for wildlife trade and farming, with thousands of licensed operations raising species such as civets, porcupines, bamboo rats, snakes, and wild boar for meat, traditional medicine, and the exotic pet trade (Van Thu et al., 2023). The sector poses significant public health risks due to the potential for transmission of novel zoonotic diseases (Latinne & Padungtod, 2025). Understanding the economics of this sector is critical to developing effective policy for managing and de-risking wildlife sup-ply chains but data is scarce, typically based on small sample sizes and limited study sites (Thuy et al., 2021). This note provides descriptive statistics regarding the economics of wildlife farming in two provinces of Vietnam, based on a survey of wildlife farming households.